2023
DOI: 10.3390/cells13010079
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Neuroinflammation in Alzheimer’s Disease

Yajing Ma,
Wang Wang,
Sufang Liu
et al.

Abstract: Alzheimer’s disease (AD) is a chronic and progressive neurodegenerative disease and clinically manifests with cognitive decline and behavioral disabilities. Over the past years, mounting studies have demonstrated that the inflammatory response plays a key role in the onset and development of AD, and neuroinflammation has been proposed as the third major pathological driving factor of AD, ranking after the two well-known core pathologies, amyloid β (Aβ) deposits and neurofibrillary tangles (NFTs). Epigenetic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 150 publications
0
1
0
Order By: Relevance
“…It has been reported that the inflammatory response of microglia and astrocytes is stimulated by aberrant epigenetic modifications of the gene promoters of cytokines like TNF-α, IL-1β, and IL-6. This leads to the formation of pathogenic Aβ deposits and neurofibrillary tangles, which ultimately cause the development and exacerbation of AD [ 58 ]. Moreover, a study performed on familial AD patients revealed hypermethylation in the promoter regions of KLF14 , encoding for a protein involved in immune cell differentiation [ 59 ].…”
Section: Correlations Between Epigenetic Alterations and Other Age-re...mentioning
confidence: 99%
“…It has been reported that the inflammatory response of microglia and astrocytes is stimulated by aberrant epigenetic modifications of the gene promoters of cytokines like TNF-α, IL-1β, and IL-6. This leads to the formation of pathogenic Aβ deposits and neurofibrillary tangles, which ultimately cause the development and exacerbation of AD [ 58 ]. Moreover, a study performed on familial AD patients revealed hypermethylation in the promoter regions of KLF14 , encoding for a protein involved in immune cell differentiation [ 59 ].…”
Section: Correlations Between Epigenetic Alterations and Other Age-re...mentioning
confidence: 99%